Challenges and advances of immune checkpoint therapy - Lingyu Li; Yingli Sun (Clinical and Translational Discovery)
Abstract Background and Objectives Immuno‐checkpoint therapy (ICT) significantly alters the clinical course of cancer patients, providing long‐lasting clinical benefits and offering the potential for cure to some patients. However, response rates for different tumour types vary, and predictive biomarkers are needed to enhance patient selection for the purpose of optimising effectiveness and reducing toxicity. This has driven efforts to decipher the immune and non‐immune factors that regulate ICT response. Main Content This review offers a thorough examination of the advantages and future challenges of immune checkpoint inhibitors in cancer therapy. Additionally, we explore ongoing efforts to address current challenges, such as guiding subsequent clinical trials, developing ICT combination therapy strategies and utilising epigenetics to enhance clinical efficacy. Conclusion and Perspectives Despite significant progress, ICT faces challenges including immune‐related adverse events (irAEs) and resistance mechanisms. Ongoing research focuses on developing novel biomarkers, combination therapies, and epigenetic strategies to improve the efficacy and safety of ICT for cancer patients worldwide. Future studies are required to validate these findings across different tumor types and treatment settings.